Detection of oligoclonal free kappa chains in the absence of oligoclonal IgG in the CSF of patients with suspected multiple sclerosis. Issue 2 (23rd January 2004) - Goffette, S; Schluep, M; Henry, H; Duprez, T; Sindic, C J M
Abstract : Background: Oligoclonal free kappa bands are present as frequently as oligoclonal IgG bands in the cerebrospinal fluid (CSF) from patients with definite multiple sclerosis (MS) and can even occur in the absence of oligoclonal IgG. As such, they too are markers of an ongoing intrathecal immune process. Objectives: To determine how frequently oligoclonal free kappa bands are detectable in the CSF from patients with clinical signs and symptoms suggestive of MS in the absence of CSF restricted oligoclonal IgG. Methods: An immunoaffinity mediated immunoblotting technique specific for free kappa chains was used, after isoelectric focusing of paired CSF and serum samples from 33 patients with clinical signs and symptoms suggestive of MS but without CSF oligoclonal IgG. CSF data were correlated with MRI results in the context of the new diagnostic criteria from McDonald et al . Results: Eighteen CSF samples contained oligoclonal free kappa bands (54%), mainly from patients with motor dysfunction (83%) and optic neuritis (64%). All patients with a positive MRI according to Barkhof's criteria (n = 6) had free kappa bands in their CSF. Conclusions: (1) Oligoclonal free kappa bands in the CSF are related to the dissemination of MS lesions; (2) such bands should be looked for in oligoclonal IgG negative CSF, and (3) the presence of free kappa bands in the CSF may be a substitute for oligoclonal IgG in the McDonald's criteria for diagnosis of MS.